Review: Challenges in the histopathological classification of ganglioglioma and DNT: microscopic agreement studies and a preliminary genotype-phenotype analysis - Blümcke, Ingmar; Wefers, Annika K.; Capper, David (Neuropathology & applied neurobiology, 2019)
Low-grade epilepsy-associated brain tumours (LEAT) are the second most common cause for drug-resistant, focal epilepsy, that is ganglioglioma (GG) and dysembryoplastic neuroepithelial tumours (DNT). However, molecular pathogenesis, risk factors for malignant progression and their frequent association with drug-resistant focal seizures remain poorly understood. This contrasts recent progress in understanding the molecular-genetic basis and targeted treatment options in diffuse gliomas. The Neuropathology Task Force of the International League Against Epilepsy examined available literature to identify common obstacles in diagnosis and research of LEAT. Analysis of 10 published tumour series from epilepsy surgery pointed to poor inter-rater agreement for the histopathology diagnosis. The Task Force tested this hypothesis using a web-based microscopy agreement study. In a series of 30 LEAT, 25 raters from 18 countries agreed in only 40% of cases. Highest discordance in microscopic diagnosis occurred between GG and DNT variants, when oligodendroglial-like cell patterns prevail, or ganglion cells were difficult to discriminate from pre-existing neurons. Suggesting new terminology or major histopathological criteria did not satisfactorily increase the yield of histopathology agreement in four consecutive trials. To this end, the Task Force applied the WHO 2016 strategy of integrating phenotype analysis with molecular-genetic data obtained from panel sequencing and 450k methylation arrays. This strategy was helpful to distinguish DNT from GG variants in all cases. The Task Force recommends, therefore, to further develop diagnostic panels for the integration of phenotype-genotype analysis in order to reliably classify the spectrum of LEAT, carefully characterize clinically meaningful entities and make better use of published literature.